Aging effects on recycled WMA porous asphalt mixtures. (1st October 2016) - Frigio, F.; Raschia, S.; Steiner, D.; Hofko, B.; Canestrari, F.
Highlights: Aging effect on warm recycled porous asphalt produced using different WMA additives. Limited short-term aging for WMA bitumen/mixture due to low production temperatures. Extensive long-term aging effects for WMA bitumens/mixtures contrarily to HMA. The organic additive tends to increase bitumen and, thus, WMA mixture stiffness. Fatigue life is not affected by low production temperature or warm additive type. Abstract: Nowadays, the use of reclaimed asphalt pavements (RAP) is often combined with Warm Mix Asphalt (WMA) technologies with several benefits in terms of environment, cost and mechanical performance. Concerns still exist related to in-service and aging characteristics of warm recycled mixtures since WMA technologies have been developed over the last decade and hence long term performance data are not available yet. The objective of this experimental study is to evaluate the aging effect on recycled porous asphalt (PA) mixtures produced at reduced temperatures using different WMA additives (organic, chemical and zeolite) and including 15% of RAP. In this sense, long term aging was simulated in the laboratory on compacted specimens by means of the Viennese Aging Procedure (VAPro). Rheological properties of the extracted bitumen samples were measured in order to evaluate possible links between bitumen and mixtures performance. As far as mixtures are concerned, stiffness tests were carried out before and after aging, whereas fatigue resistance was evaluated on long term aged mixtures to compare long term performance of HMA and WMA porous asphalt. Mixtures as well as bitumens results showed that the lower aging process that WMA mixtures undergo during production affects mixtures stiffness at the beginning of service life. Only the presence of the organic additive increases the stiffness of WMA bitumens and mixtures due to the crystalline network structure that forms in the bitumen. On the other hand, extensive long term aging effects were measured in case of WMA mixtures. Nonetheless, overall fatigue results showed that long term fatigue performance of WMA mixtures are not significantly affected compared to HMA regardless of WMA additive types.